N. Katanov, an accumulator of the Tuvan folklore - Kungaa, Margarita B. (The New Research of Tuva, 2009)
Article deals with folklore pieces accumulated by Nikolay Katanov during his research expedition over Tuva made in 1889. The scholar accumulated folklore materials quite various both in essence and genre comprising unique and rare records.